A Systematic Review of Diagnostic Radiology Access, Barriers, and Novel Interventions in Low-Income Countries - Belladina Mayyasha Martadipura; Raudina Fisabila Martadipura (International Medical Journal Corp. Ltd, 2025)
Introduction: Diagnostic radiology is an essential component of modern healthcare, yet billions of people in Low-Income Countries (LICs) lack access. This disparity, which impacts outcomes for both communicable and non-communicable diseases, remains a neglected area in global health policy. This review systematically synthesizes the evidence on radiology access, barriers, and the impact of novel interventions in LICs. Methods: This systematic review was conducted following PRISMA guidelines. We searched PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library for studies published between 1 January 2018 and 31 December 2025. We included primary studies and surveys focused on LICs (per World Bank GNI ≤ 1,135) that reported on outcomes related to radiology access, barriers, or interventions. Quality assessment was performed using the ROBINS-I and Newcastle-Ottawa Scale (NOS) tools. Results: Sixteen studies met the inclusion criteria. The results demonstrate a significant and catastrophic deficit in conventional imaging and workforce, with less than one CT scanner per million inhabitants in LICs and diagnostic availability near 0% at the primary care level. This gap is linked to severe outcome disparities, including a 3-month stroke mortality rate 4.5 times higher in LMICs than in HICs (7.7% vs. 1.7%). However, the review also identified significant evidence for novel interventions. Teleradiology implementation in the Democratic Republic of Congo changed patient diagnosis in 62% of cases and management in 41%. AI-assisted diagnostics show significant cost-effectiveness for conditions like tuberculosis in Malawi. Point-of-Care Ultrasound (POCUS) emerges as a critical, high-impact tool, though its implementation remains profoundly limited. Discussion: The evidence confirms a